2020
DOI: 10.1097/md.0000000000021597
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic response to corticosteroids in a critically ill patient with COVID-19

Abstract: Introduction: Since the coronavirus disease 2019 (COVID-19) outbreak in Wuhan in late 2019, controversy on the use of corticosteroids for COVID-19 has obtained increasing attention. We present 1 critically ill patient who had a rapid therapeutic response to moderate-dose corticosteroids. Patient concerns: A 53-year-old critically ill woman from Wuhan suffered with COVID-19. Diagnosis: The chest computed tomography scan was suggestive of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…The outcome of CSs among the treated COVID-19 patients is found to vary due to different doses. To mitigate the uncertainty, CSs could be used at a moderate dose for a shorter period [ 91 ]. A detailed medical history of the patients should be collected before treating with CSs to minimize CSs induced comorbidity.…”
Section: Recommendations To Minimize the Side Effects Of Css Treatment In Covid-19 Patientsmentioning
confidence: 99%
“…The outcome of CSs among the treated COVID-19 patients is found to vary due to different doses. To mitigate the uncertainty, CSs could be used at a moderate dose for a shorter period [ 91 ]. A detailed medical history of the patients should be collected before treating with CSs to minimize CSs induced comorbidity.…”
Section: Recommendations To Minimize the Side Effects Of Css Treatment In Covid-19 Patientsmentioning
confidence: 99%
“…[ 35 ] Patients with severe conditions were more likely to require glucocorticoids. [ 36 ] Our findings showed that using glucocorticoid could reduce the mortality of severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 75%
“…The ocular findings of this patient improved following topical and systemic corticosteroid therapy which was tapered over a period of six weeks. A recent case report 17 showed that early use of corticosteroids at a moderate dose for a short course may enhance recovery of a COVID-19 patient. In this context, we support timely and appropriate use of corticosteroids in COVID-19 cases taking into consideration uveitis severity, systemic comorbidities, age, and lens status.…”
Section: Discussionmentioning
confidence: 99%